2022
DOI: 10.1039/d2cp02820d
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating ab initio QM/MM free energy simulations by Gaussian process regression with derivative observations

Abstract: In this machine-learning-facilitated method, Gaussian process regression (GPR) is used to predict energy and force corrections for a semiempirical QM/MM level to match with ab initio QM/MM results during MD-based free energy simulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 87 publications
2
7
0
Order By: Relevance
“…This way, our results are consistent with previous observations that the AM1/TIP3P level of theory overestimates the reaction barrier (and underestimates the reaction exergonicity), in comparison with the closely related reaction between NH 3 and MeI. It has been shown that further corrections of the Menshutkin’s reaction path and the associated free energies can be performed with a machine learning-based refinement of the MFEP computed at the AM1/TIP3P level of theory . However, in this work, we will focus the following discussion on the comparison with precedents at AM1 level of theory.…”
Section: Results and Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This way, our results are consistent with previous observations that the AM1/TIP3P level of theory overestimates the reaction barrier (and underestimates the reaction exergonicity), in comparison with the closely related reaction between NH 3 and MeI. It has been shown that further corrections of the Menshutkin’s reaction path and the associated free energies can be performed with a machine learning-based refinement of the MFEP computed at the AM1/TIP3P level of theory . However, in this work, we will focus the following discussion on the comparison with precedents at AM1 level of theory.…”
Section: Results and Discussionsupporting
confidence: 92%
“…Both FENEB and US produce practically the same trajectory in regions 1 and 3, being the most important differences located in the region of the transition ensemble. In the case of the FENEB path, the variation in the middle zone is quite linear, in good agreement with previous reports. , On the other hand, the path obtained with US differs mainly in the d C–Cl branch. Nevertheless, both methods obtain, in this case, almost the same coordinates for the maximum free energy value, which can be noted by the cross marks.…”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations